The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.21037/sci.2016.11.16
|View full text |Cite
|
Sign up to set email alerts
|

The silver lining of induced pluripotent stem cell variation

Abstract: Induced pluripotent stem cells (iPSCs) are being generated using various reprogramming methods and from different cell sources. Hence, a lot of effort has been devoted to evaluating the differences among iPSC lines, in particular with respect to their differentiation capacity. While line-to-line variability should mainly reflect the genetic diversity within the human population, here we review some studies that have brought attention to additional variation caused by genomic and epigenomic alterations. We disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…Lastly, several groups reported that variation in routine cell culturing and maintenance such as variation in passage number, growth rate and culture medium contribute to iPSC variability (Fossati et al, 2016;Hu et al, 2010;Schwartzentruber et al, 2018;Volpato et al, 2018), and that automated platforms can reduce such variability (Paull et al, 2015). Our own group has also recently shown that laboratory-based sources of variation, even when different laboratories follow standardised protocols, can substantially overpower genotypic effects.…”
Section: Non-genetic Variationmentioning
confidence: 99%
“…Lastly, several groups reported that variation in routine cell culturing and maintenance such as variation in passage number, growth rate and culture medium contribute to iPSC variability (Fossati et al, 2016;Hu et al, 2010;Schwartzentruber et al, 2018;Volpato et al, 2018), and that automated platforms can reduce such variability (Paull et al, 2015). Our own group has also recently shown that laboratory-based sources of variation, even when different laboratories follow standardised protocols, can substantially overpower genotypic effects.…”
Section: Non-genetic Variationmentioning
confidence: 99%
“…1 a (i, ii)). These cells were differentiated into reconditioned monocytes (RM) by culturing them in media consisting IL-3, MCSF and β-ME in a low serum environment as reported earlier [ 17 ]. The monocytes upon de-differentiation became larger in size, rounded and formed colonies by day 6 in culture (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A troublesome aspect of processes that concur with cell dedifferentiation is the accentuated heterogeneity detected at genetic, epigenetic, and phenotypic levels ( Almendro, Marusyk & Polyak, 2013 ; Burrell et al, 2013 ; Fossati, Jain & Sevilla, 2016 ; Krishna et al, 2016 ; Ling et al, 2015 ; Meacham & Morrison, 2013 ). Such heterogeneities are of great concern because they can limit the response to treatment of cancerous cell, or the reproducibility of healthy clonal tissues and individuals derived from animal and plant induced dedifferentiated cells ( Almendro, Marusyk & Polyak, 2013 ; Burrell et al, 2013 ; Fossati, Jain & Sevilla, 2016 ; Krishna et al, 2016 ; Ling et al, 2015 ; Meacham & Morrison, 2013 ). Intriguingly, a chromatin relaxation-based extensive reduction in gene expression heterogeneity for dedifferentiated cells could promote long-term phenotypic heterogeneities following cell dedifferentiation by increasing genetic and epigenetic mutagenic potential and the phenotypic relevance of preexisting or newly generated mutations for dedifferentiated cells.…”
Section: Discussionmentioning
confidence: 99%